The Relationship Between Preoperative Inflammatory Indexes and Adherent Perinephric Fat in Laparoscopic Partial Nephrectomy: The Preoperative Predictive Factors for Laparoscopic Partial Nephrectomy - Çil, Gökhan; Yilmaz, Mehmet; Yentur, Serhat; Çolakerol, Aykut; Canıtez, İbrahim Ogulcan (Scripta Medica, 2024)
Background/Aim: Partial nephrectomy (PN) is favoured for cT1a renal tumours. However, factors like adherent perinephric fat (APF), linked to prolonged operation time due to chronic inflammation are often overlooked. The objective of this study was to assess the relationship between the composite inflammatory index and APF in patients with renal cell carcinoma (RCC) prior to laparoscopic partial nephrectomy (LPN). Methods: The retrospective analysis included 189 LPN patients from April 2015 to June 2021, categorised by APF presence. Demographic, laboratory and radiological data assessed composite inflammatory index and Mayo adhesion probability (MAP) scores. Chi-Square and Mann-Whitney U-test analysed categorical and continuous variables. Area under curve (AUC) measured parameter discrimination. Logistic regression identified APF predictive factors. Results: APF was present in 90 patients (47.6 %). The APF-positive group had significantly higher C-reactive protein (CRP) levels and longer operation times (p = 0.016 and p = 0.001, respectively). Elevated MAP scores and systemic inflammatory index (SII) values were also observed in the APF-positive group (p = 0.002 and p = 0.001, respectively). Receiver operating characteristic (ROC) analysis determined SII’s cut-off at 600 (sensitivity: 60.0 %, specificity: 60.6 %, AUC: 0.640, p = 0.001), MAP score at 2.5 (sensitivity: 67.8 %, specificity: 64.5 %, AUC: 0.640, p < 0.001) and operation time at 122.5 min (sensitivity: 74.4 %, specificity: 67.7 %, AUC: 0.807, p < 0.001). Conclusion: Presented results indicate that SII is linked to APF in patients undergoing LPN and may serve as an independent predictor of APF positivity.